Comparison of risk adjusted excess post‐operative pancreatic fistula rates after pancreaticoduodenectomy using cumulative sum analysis. Issue 7 (17th May 2022) - Lockie, Elizabeth B.; Knowles, Brett; Gill, Patwinder K.; Thomson, Benjamin; Loveday, Benjamin P. T.
Abstract: Background: Post‐operative pancreatic fistula (POPF) is a key outcome post pancreaticoduodenectomy. There are numerous POPF risk calculators but no agreed benchmark, a key component of meaningful audit. We compared observed versus predicted POPF for six risk adjusted POPF calculators, to ascertain how they differ and thus contribute to discussion around benchmarking. Methods: This was a retrospective single‐arm cohort study at the Royal Melbourne Hospital of patients who underwent pancreaticoduodenectomy 1 November 2015 to 31 December 2021 with a primary outcome of a clinically relevant POPF. Cumulative sum (CUSUM) plots of observed versus predicted rate of POPF for sequential patients were constructed for six risk adjusted POPF calculators – Birmingham, updated Birmingham, fistula risk score (FRS), modified FRS (m‐FRS), alternative FRS (a‐FRS), and updated alternative FRS (ua‐FRS). Results: The study included 77 patients. The actual rate of clinically relevant POPF was 14.3%. FRS calculated an excess of 1.3 POPF per 100 cases. All other calculators demonstrated prevention of POPF per 100 cases: Birmingham 3.4, updated Birmingham 14.0, m‐FRS 0.3, a‐FRS 1.2, ua‐FRS 19.7. Conclusion: The observed versus predicted rate of POPF was near zero for all risk calculators except ua‐FRS and updated Birmingham, which predicted a higher POPF than observed (19.7, 14.0, respectively). These results indicate that, excepting ua‐FRS and updated Birmingham, these calculators yield comparable results. Benchmarks for POPF should prescribe which risk calculators are used, and ideally a unified standard between centres should be the goal to provide consistency in outcome reporting and robust audit processes. Abstract : The observed versus predicted rate of clinically POPF was near zero for all risk calculators except ua‐FRS, which predicted a higher POPF than observed. These results indicate that, excepting ua‐FRS, these risk calculators yield comparable results. Benchmarks for POPF should prescribe which risk calculators are used, and ideally a unified standard between centres should be the goal to provide consistency in outcome reporting and robust audit processes.